2014
DOI: 10.5539/res.v6n2p1
|View full text |Cite
|
Sign up to set email alerts
|

Locomotor Development of Children Aged 3.5 to 5 Years in Nursery Schools in Greece

Abstract: The present study was designed to examine the effect of an intervention program on nursery school children's locomotor development. Participants were 98 children (50 boys and 48 girls) aged 3.5-5 from three preschools of the Municipality of Kalamaria, in Greece. The 49 children who formed the experimental group participated for two months in 16 organised courses, designed to develop basic motor skills. The measurement tool used to evaluate the sample before and after the intervention was Urlich's test of gross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(35 citation statements)
references
References 24 publications
(22 reference statements)
2
31
0
2
Order By: Relevance
“…[17][18][19][20][21] Three studies were conducted in the USA 17 18 22 two studies were conducted in Australia 20 23 and the others were conducted in Switzerland 19 and Greece. 21 Some studies recruited centres based on region 19 21 or within an existing program 17 while others worked together with the (local) government 23 or childcare organisations. 18 20 22 Two studies involved parents.…”
Section: Overview Of Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…[17][18][19][20][21] Three studies were conducted in the USA 17 18 22 two studies were conducted in Australia 20 23 and the others were conducted in Switzerland 19 and Greece. 21 Some studies recruited centres based on region 19 21 or within an existing program 17 while others worked together with the (local) government 23 or childcare organisations. 18 20 22 Two studies involved parents.…”
Section: Overview Of Studiesmentioning
confidence: 99%
“…There were six randomised controlled trials 17-19 20 22 23 and one quasi-experimental study. 21 The sample size of the studies varied from 71 17 to 835 participants. 19 Implementation All interventions took place in early childhood settings and most were delivered by setting staff.…”
Section: Overview Of Studiesmentioning
confidence: 99%
“…The main principles of motor development are maturing, sequence, motivation, experience, and practice. The results of Tsapakidou et al, (2014) research showed that suitable, good formed movement programs can develop children's fundamental movement skills. Physical development in children was characterized by the development of gross and fine motor skills.…”
Section: Introductionmentioning
confidence: 99%
“…In that way, the importance of movement development before kindergarten school is emphasised. Consequently, educators are being ncouraged to utilize children's natural inclination for movement and to integrate organised motor skills programs into their daily schedule [9]. The result of the third hypothesis test states that the fundamental motor skill of kindergarten students is influenced by their nutrition status.…”
Section: The Significance and Linear Regression Of Nutrition Status (mentioning
confidence: 99%